Chemical characteristics of the Bandaiko hyper-acidic hot spring in Kusatsu Town, Gunma prefecture, and evaluation test of scale for binary power generation - Mio Ichino; Toshio Inoue; Yuka Kubotsu; Hideo Takizawa; Yukiko Hoshino; Daisuke Tanaka; Akira Ueda; Hideki Kuramitz (Geothermics, 2027)

Electromethanogenesis for efficient CO2 conversion to CH4 generation: Fundamental drivers, microbial interactions, and improvement strategies - Lucky Caesar Direstiyani; Daisuke Inoue; Michihiko Ike (Journal of Environmental Chemical Engineering, 2026)

Zinc-dependent prothrombin activator from Rhabdophis tigrinus venom with extended substrate specificity - Noboru Inoue; Yoshihiko Sakurai; Kyoko Hasuwa; Katsuya Yuui; Risa Kudo; Tomohiro Takeda; Takumi Takata; Daisuke Sasaki; Masanori Matsumoto; Yoshihiro Fujimura; Shogo Kasuda (Toxicon, 2026)

Comparison of Predatory Phenotypes and Genotypes Between Bdellovibrio sp. BIS2 and Bacteriovorax sp. HI3 Isolated From the Same Freshwater Environment - Tomomi Sugiyama; Tsubasa Kojima; Naoki A. Uemura; Daisuke Nakane; Hideo Dohra; Daisuke Inoue; Michihiko Ike (Environmental Microbiology, 2026)
Bdellovibrio and like organisms (BALOs) are predatory bacteria, which play crucial roles in shaping community structure and maintaining diversity in microbial ecosystems. However, functional and genetic variation among coexisting BALOs remains largely unexplored. Here, we characterised Bdellovibrio sp. BIS2 and Bacteriovorax sp. HI3, which were isolated from the same freshwater environment at different time points. Predation assays and a functional genomic analysis revealed that the predators have distinct prey ranges and predatory behaviours with associated genotypic differences, which may contribute to niche partitioning in the shared habitat. BIS2 possessed an extensive set of flagellar genes, likely contributing to its higher motility and rapid spatial exploration. However, cell debris remained after predation because the prey cells were incompletely lysed. HI3 displayed efficient localised predation and thorough lysis of prey cellular components. The difference in predation efficiency was likely attributed to distinct profiles of hydrolytic enzymes in the two BALOs, including enzymes critical for prey cell lysis and exit from the prey. Genomic regions unique to each predator with predation‐associated genes suggest that genetic divergence drove the evolution of specialised predatory properties across BALOs. These findings provide insights into variation in predatory traits among BALOs, a key mechanism enabling coexistence and adaptation.

Bioplastic production potential, growth optimization, and biokinetics of methane-oxidizing bacterium Methylosinus sp. strain C49 - Jameil Magomnang; Shohei Yasuda; Daisuke Inoue; Akihiko Terada (Bioresource Technology, 2025)

Flow regimes of R32, R1234yf, and R454C in horizontal multiport mini/micro-channels: Development of a new flow regime prediction method - Taiga Nogami; Daisuke Jige; Norihiro Inoue (International Journal of Refrigeration, 2025)

Duckweed as an Emerging Model System for Plant–Microbiome Interactions - Hidehiro Ishizawa; Yuparat Saimee; Tomomi Sugiyama; Tsubasa Kojima; Daisuke Inoue; Michihiko Ike; Arinthip Thamchaipenet; Masaaki Morikawa (Environmental Microbiology, 2025)
Understanding the processes through which plant‐associated microbiomes influence host physiology and fitness is a central goal of plant–microbiome interaction research. While traditional model plants such as Arabidopsis thaliana have provided foundational platforms to examine these processes, alternative model systems may address certain bottlenecks in current research. In recent years, duckweeds (family Lemnacea) have emerged as a unique model plant offering several experimental advantages owing to their small size, simple morphology, aquatic habitat, and two‐dimensional clonal growth. These features facilitate the establishment of highly tractable and reproducible model systems that facilitate robust investigations and high‐throughput screening platforms, enabling multifactorial massive parallel experiments. This review provides an overview of the recent studies that have applied the advantages of using duckweed in the field of plant–microbiome interactions to highlight how duckweed‐based systems have enabled unique experimental approaches that are difficult in conventional systems. We have also discussed the emerging directions in duckweed–microbiome research, including elucidation of the co‐evolutionary processes mediated via metabolic exchange and bottom‐up explanation of community structure and functions using synthetic bacterial communities. Together, this review underscores the potential of duckweed to serve as a distinctive model for advancing plant–microbiome interaction research.

Combined inhibition of anaerobic digestion by sulfate, salinity, and ammonium: potential inhibitory factors in forward osmosis-concentrated municipal wastewater - Luong Van Duc; Daisuke Inoue; Michihiko Ike (Chemosphere, 2025)

Annual reproductive cycle of the pen shell Atrina pectinata in Mikawa Bay, Japan - Yuki Hirano-Maeda; Daisuke Ojima; Shunsuke B. Inoue; Masaei Kanematsu (Invertebrate Reproduction & Development, 2025)

FATP1-mediated fatty acid uptake in renal tubular cells as a countermeasure for hypothermia - Kie Horioka; Hiroki Tanaka; Shimpei Watanabe; Shinnosuke Yamada; Shuhei Takauji; Akira Hayakawa; Shotaro Isozaki; Keisuke Okaba; Namiko Ishii; Ayumi Motomura; Hiroyuki Inoue; Lynda Addo; et al. (Journal of Molecular Medicine, 2025)
Hypothermia is a condition in which body temperature falls below 35 °C, resulting from exposure to low environmental temperatures or underlying medical conditions. Postmortem examinations have revealed increased levels of fatty acids in blood and lipid droplet formation in renal tubules during hypothermia. However, the causes and implications of these findings are unclear. This study aimed to analyze the biological significance of these phenomena through lipidomics and transcriptomics analyses of specimens from emergency hypothermia patients and mouse hypothermia models. Both human hypothermia patients and murine models exhibited elevated plasma concentrations of fatty acids and their derivatives compared with controls. Hypothermic mouse kidneys displayed lipid droplet formation, with gene expression analysis revealing enhanced fatty acid uptake and β-oxidation in renal tubular cells. In primary cultured mouse renal proximal tubular cells, low temperatures increased the expression levels of Fatty acid transport protein 1 (FATP1), a fatty acid transporter, and boosted oxygen consumption via β-oxidation. Mice treated with FATP1 inhibitors showed a more rapid decrease in body temperature upon exposure to low temperatures compared with untreated mice. In conclusion, increased fatty acid uptake mediated by FATP1 in renal tubular cells plays a protective role during hypothermia. Key messages Low temperatures increase FATP1 expression and fatty acid uptake in renal proximal tubular cells, resulting in enhanced β-oxidation. Renal proximal tubular cells play an important role in the resistance to hypothermia via lipid uptake. Maintaining renal lipid metabolism is essential for cold stress adaptation.

Establishment of a human ovarian endometrioid carcinoma cell line by constitutive expression of cyclin-dependent kinase 4, cyclin D1 and telomerase reverse transcriptase - Hitomi Hoshino; Tomoya O. Akama; Daisuke Inoue; Suzuko Moritani; Shohei Shigeto; Kazuyuki Matsuda; Hisato Yoshida; Natsumi Yonemoto; Mana Fukushima; Yoshio Yoshida; Motohiro Kobayashi (Human Cell, 2025)
Only a few human ovarian endometrioid carcinoma cell lines are currently available, partly due to the difficulty of establishing cell lines from low-grade cancers. Here, using a cell immortalization strategy consisting of i) inactivation of the p16 INK4a -pRb pathway by constitutive expression of mutant cyclin-dependent kinase 4 (R24C) (CDK4 R24C ) and cyclin D1, and ii) acquisition of telomerase reverse transcriptase (TERT) activity, we established a human ovarian endometrioid carcinoma cell line from a 46-year-old Japanese woman. That line, designated JFE-21, has proliferated continuously for over 6 months with a doubling time of ~ 55 h. JFE-21 cells exhibit polygonal shapes and proliferate without contact inhibition to form a monolayer in a jigsaw puzzle-like arrangement. Ultrastructurally, JFE-21 cells exhibit well-developed rough endoplasmic reticulum, mitochondria and lysosomes in the cytoplasm, with cells contacting each other via desmosomes. G-band karyotype analysis indicated that cells had a near-tetraploid karyotype. Immunofluorescence staining revealed that the expression profile of a series of ovarian carcinoma markers in JFE-21 cells was consistent with ovarian endometrioid carcinoma. Moreover, Sanger sequencing of DNA polymerase ε ( POLE ) gene and immunohistochemical analysis of mismatch repair (MMR) proteins revealed that JFE-21 cells were classified as the no specific molecular profile (NSMP) subtype. In addition, JFE-21 cells were sensitive to paclitaxel and carboplatin administered to the donor as therapy. These findings indicate that constitutive expression of CDK4 R24C , cyclin D1 and TERT genes may be an option to establish cell lines from low-grade cancers, including ovarian endometrioid carcinoma.

Uncovering the causal relationships in plant-microbe ecosystems: A time series analysis of the duckweed cultivation system for biomass production and wastewater treatment - Hidehiro Ishizawa; Yosuke Tashiro; Takashi Okada; Daisuke Inoue; Michihiko Ike; Hiroyuki Futamata (Science of The Total Environment, 2024)

Different bioaugmentation regimes that mitigate ammonium/salt inhibition in repeated batch anaerobic digestion: Generic converging trend of microbial communities - Zi-Yan Li; Shintaro Nagao; Daisuke Inoue; Michihiko Ike (Bioresource Technology, 2024)

The past, present, and a future for native charr in Japan - Kurt D. Fausch; Kentaro Morita; Jun-ichi Tsuboi; Yoichiro Kanno; Shoichiro Yamamoto; Daisuke Kishi; Jason B. Dunham; Itsuro Koizumi; Koh Hasegawa; Mikio Inoue; Takuya Sato; Satoshi Kitano (Ichthyological Research, 2024)
Charrs ( Salvelinus ) reach their southernmost distribution in Japan, and are uniquely adapted to the short, steep streams of this island archipelago. Southern Asian Dolly Varden ( Salvelinus curilus ) occur only in Hokkaido Island, whereas white-spotted charr ( Salvelinus leucomaenis ) range to southern Honshu. Both species diverged from an ancestral lineage during the late Pliocene/early Pleistocene, when lowered sea levels created semi-enclosed water bodies in the seas of Japan and Okhotsk. Genetic analyses showed S. curilus represents the most ancient divergence from the Dolly Varden ( Salvelinus malma ) - Arctic charr ( Salvelinus alpinus ) group, and revealed five lineages of S. leucomaenis which align differently than traditional subspecies. Japanese charr display diverse and flexible life histories including anadromous fish with partial migration, and fluvial, adfluvial, and resident forms. In Hokkaido, Dolly Varden are distributed upstream and white-spotted charr downstream. They coexist in narrow sympatric zones through adaptive shifts by Dolly Varden in behavior and morphology that facilitate benthic foraging. Both species hybridize with native and nonnative salmonids, and are displaced from microhabitats and decline in abundance when rainbow trout ( Oncorhynchus mykiss ) and brown trout ( Salmo trutta ) invade. Japan streams contain over 95,000 erosion control dams which create short stream fragments (medians ~200 m). This has increased extirpation of charr populations via lower genetic diversity and stochastic and demographic factors. Tributaries provide complex rearing habitats, afford refuges from floods, and supply recruits that sustain populations in mainstem fragments and create metapopulations in connected riverscapes. Charr play central roles in linked stream-riparian food webs, and cause direct and indirect effects that cascade to streambed algae and riparian predators when linkages are disrupted by anthropogenic effects or altered by native parasites. Many charr populations are threatened by habitat fragmentation and introgression or invasion by nonnative forms, but efforts to conserve charr are growing. These include restoring connectivity among pure populations above barriers that prevent invasions, protecting tributary nurseries, and instituting angling regulations to protect headwater populations. Key steps include inventorying pure populations, identifying conservation units, selecting appropriate management based on connectivity and biotic interactions, and engaging stakeholders and youth to engender an ethic for conserving irreplaceable charr lineages.

Resource partitioning between non-native white-spotted charr and native red-spotted masu salmon in Shikoku, southwestern Japan: population- and individual-level analyses - Daisuke Togaki; Mikio Inoue; Hayato Kawaguchi; Keita Yamamoto (Ichthyological Research, 2024)

Web application of an integrated simulation for aquatic environment assessment in coastal and estuarine areas - Yoshitaka Matsuzaki; Tetsunori Inoue; Masaya Kubota; Hiroki Matsumoto; Tomoyuki Sato; Hikari Sakamoto; Daisuke Naito (Environmental Modelling & Software, 2024)

Prolonged exposure to hypergravity increases number and size of cells and enhances lignin deposition in the stem of Arabidopsis thaliana - Hironori Shinohara; Masaki Muramoto; Daisuke Tamaoki; Hiroyuki Kamachi; Hiroshi Inoue; Atsushi Kume; Ichirou Karahara (Journal of Plant Research, 2024)

Effects of different exercise modes and intensities on cognitive performance, adult hippocampal neurogenesis, and synaptic plasticity in mice - Hanlin Jiang; Yusuke Kimura; Shota Inoue; Changxin Li; Junpei Hatakeyama; Masahiro Wakayama; Daisuke Takamura; Hideki Moriyama (Experimental Brain Research, 2024)

Transgenerational acclimation to acidified seawater and gene expression patterns in a sea urchin - Akira Iguchi; Kodai Gibu; Makiko Yorifuji; Miyuki Nishijima; Atsushi Suzuki; Tsuneo Ono; Yukio Matsumoto; Mayuri Inoue; Masahiko Fujii; Daisuke Muraoka; Yamato Fujita; Hideki Takami (Science of The Total Environment, 2024)

Establishment of a human ovarian clear cell carcinoma cell line mutant in PIK3CB but not PIK3CA - Hitomi Hoshino; Daisuke Inoue; Akiko Shinagawa; Hisato Yoshida; Shohei Shigeto; Kazuyuki Matsuda; Tomoya O. Akama; Yoshio Yoshida; Motohiro Kobayashi (Human Cell, 2024)
A human ovarian clear cell carcinoma cell line was established from a 46-year-old Japanese woman. That line, designated MTC-22, has proliferated continuously for over 6 months in conventional RPMI 1640 medium supplemented with 10% foetal bovine serum and has been passaged over 50 times. MTC-22 doubling-time is ~ 18 h, which is much shorter than most ovarian clear cell carcinoma lines reported to date. Morphologically, MTC-22 cells exhibit polygonal shapes and proliferate to form a monolayer in a jigsaw puzzle-like arrangement without contact inhibition. Ultrastructurally, cells exhibit numerous intracytoplasmic glycogen granules and well-developed mitochondria. G-band karyotype analysis indicated that cells have a complex karyotype close to tetraploid. We observed that the expression pattern of a series of ovarian carcinoma-related molecules in MTC-22 cells was identical to that seen in the patient’s tumour tissue. Notably, MTC-22 cells, and the patient’s carcinoma tissue, expressed low-sulphated keratan sulphate recognised by R-10G and 294-1B1 monoclonal antibodies, a hallmark of non-mucinous ovarian carcinoma, and particularly of clear cell ovarian carcinoma. Moreover, characteristic point mutations—one in ARID1A , which encodes the AT-rich interaction domain containing protein 1A, and the other in PIK3CB, which encodes the catalytic subunit of phosphoinositide 3-kinase—were seen in the patient’s tumour tissue and retained in MTC-22 cells. Collectively, these findings indicate that MTC-22 cells could serve as a valuable tool for investigating the pathophysiology of ovarian clear cell carcinoma, particularly that harbouring PIK3CB mutations, and for developing and validating new diagnostic and therapeutic approaches to this life-threatening malignancy.

Congenital malformations caused by Akabane virus in porcine fetuses in southern Japan - Daisuke Inoue; Akimi Hayashima; Fumiko Suzuta; Yasuhiko Motomura; Yuta Kawamoto; Fumihiko Yoshino; Kotaro Morita; Yoshio Hirai; Shigeru Iwamatsu; Satoshi Nakazato; Kumiko Kimura; Tohru Yanase (Veterinary Research Communications, 2024)

Enhancement of nutrient removal in an activated sludge process using aerobic granular sludge augmentation strategy with ammonium-based aeration control - Masaki Miyake; Yoshiaki Hasebe; Kazuki Furusawa; Hiroshi Shiomi; Daisuke Inoue; Michihiko Ike (Chemosphere, 2023)

Supporting table grape berry thinning with deep neural network and augmented reality technologies - Prawit Buayai; Kabin Yok-In; Daisuke Inoue; Hiromitsu Nishizaki; Koji Makino; Xiaoyang Mao (Computers and Electronics in Agriculture, 2023)

Effect of flow direction on evaporation flow regime of R32/R1234ze(E) mixture inside multiple rectangular minichannels - Natsumi Numata; Daisuke Jige; Norihiro Inoue (International Journal of Refrigeration, 2023)

Condensation flow visualization, heat transfer, and pressure drop in printed circuit heat exchangers with straight and wavy microchannels - Tatsuki Goto; Daisuke Jige; Norihiro Inoue; Kentaro Sagawa (International Journal of Refrigeration, 2023)

Bioaugmentation with marine sediment-derived microbial consortia in mesophilic anaerobic digestion for enhancing methane production under ammonium or salinity stress - Luong Van Duc; Shintaro Nagao; Mohammad Mojarrad; Yuta Miyagawa; Zi-Yan Li; Daisuke Inoue; Takahisa Tajima; Michihiko Ike (Bioresource Technology, 2023)

Mitigating ammonia-inhibition in anaerobic digestion by bioaugmentation: A review - Zi-Yan Li; Daisuke Inoue; Michihiko Ike (Journal of Water Process Engineering, 2023)

Pilot-scale demonstration of aerobic granular sludge augmentation applied to continuous-flow activated sludge process for the treatment of low-strength municipal wastewater - Masaki Miyake; Yoshiaki Hasebe; Kazuki Furusawa; Hiroshi Shiomi; Daisuke Inoue; Michihiko Ike (Journal of Water Process Engineering, 2023)

Seasonal habitat use by warmwater fishes in a braided river, southwestern Japan: effects of spatiotemporal thermal heterogeneity - Daisuke Togaki; Mikio Inoue; Kentaro Ikari (Ichthyological Research, 2023)

Complementary distribution of non-native white-spotted charr and native red-spotted masu salmon in Shikoku Island, southwestern Japan: a consequence of interspecific interactions? - Mikio Inoue; Daisuke Ichimori; Hirofumi Abe; Nobuhiko Mizuno (Ichthyological Research, 2023)

Methods for selenium removal from contaminated waters: a review - Eric Lichtfouse; Nadia Morin-Crini; Corina Bradu; Youssef-Amine Boussouga; Mehran Aliaskari; Andrea Iris Schäfer; Soumya Das; Lee D. Wilson; Michihiko Ike; Daisuke Inoue; Masashi Kuroda; Sébastien Déon; et al. (Environmental Chemistry Letters, 2022)

Route selection by fish during post-spate movement in a braided river: a potential effect on local assemblages - Daisuke Togaki; Mikio Inoue; Youhei Shiota; Yoshikado Fujimi; Ryota Kawanishi (Limnology, 2022)

Identification of novel yolk ferritins unique to planarians: planarians supply aluminum rather than iron to vitellaria in egg capsules - Osamu Kawase; Hisashi Iwaya; Yoshiya Asano; Hiromoto Inoue; Seiya Kudo; Motoki Sasahira; Nobuyuki Azuma; Daisuke Kondoh; Madoka Ichikawa-Seki; Xuenan Xuan; Kimitoshi Sakamoto; Hikaru Okamoto; et al. (Cell and Tissue Research, 2021)

Rubredoxin from the green sulfur bacterium Chlorobaculum tepidum donates a redox equivalent to the flavodiiron protein in an NAD(P)H dependent manner via ferredoxin-NAD(P)+ oxidoreductase - Wanwipa Ittarat; Takeshi Sato; Masaharu Kitashima; Hidehiro Sakurai; Kazuhito Inoue; Daisuke Seo (Archives of Microbiology, 2021)

Starting position effects in the measurement of the postural vertical for pusher behavior - Kazuhiro Fukata; Kazu Amimoto; Yuji Fujino; Masahide Inoue; Mamiko Inoue; Yosuke Takahashi; Daisuke Sekine; Shigeru Makita; Hidetoshi Takahashi (Experimental Brain Research, 2020)

Virucidal Efficacy of Olanexidine Gluconate as a Hand Antiseptic Against Human Norovirus - Kaoru Imai; Akifumi Hagi; Yasuhide Inoue; Mohan Amarasiri; Daisuke Sano (Food and Environmental Virology, 2020)
Human noroviruses are the major cause of non-bacterial acute gastroenteritis worldwide. Since no therapeutic agent has been proven to prevent human norovirus infection yet, preventive healthcare interventions to block the infection routes play an important role in infection control. One of the possible infection routes of human noroviruses are through contaminated hands, but no hand antiseptics have been proven effective. Olanexidine gluconate is a new biguanide compound that has already been approved for sale as an antiseptic for the surgical field in Japan. A new hand antiseptic was developed using olanexidine gluconate in this study, and its virucidal efficacy against human noroviruses was evaluated using modified RT-qPCR that can account for genome derived from intact viruses using RNase A and photo-reactive intercalators. We tested the virucidal efficacy of five materials; two olanexidine gluconate antiseptics (hand rub formulation and surgical field formulation), two kinds of ethanol solutions at different pH (approx. 3 or 7), and a base component of olanexidine gluconate hand rub formulation against 11 human norovirus genotypes by culture-independent methods. The infectivity of murine norovirus (MNV), a surrogate for human norovirus, was significantly reduced after use of the antiseptics. The olanexidine gluconate hand rub demonstrated the strongest virucidal efficacy against human norovirus among the five tested materials. This study showed that olanexidine gluconate has the potential to become a strong tool for the prevention of human norovirus infection.

Carbon sources that enable enrichment of 1,4-dioxane-degrading bacteria in landfill leachate - Daisuke Inoue; Kazuki Hisada; Takuya Okumura; Yoshinori Yabuki; Gen Yoshida; Masashi Kuroda; Michihiko Ike (Biodegradation, 2020)

Application of a Microreactor to Pharmaceutical Manufacturing: Preparation of Amorphous Curcumin Nanoparticles and Controlling the Crystallinity of Curcumin Nanoparticles by Ultrasonic Treatment - Kaeko Araki; Mai Yoshizumi; Shunsuke Kimura; Akiko Tanaka; Daisuke Inoue; Tomoyuki Furubayashi; Toshiyasu Sakane; Masakazu Enomura (AAPS PharmSciTech, 2020)

1,4-Dioxane degradation characteristics of Rhodococcus aetherivorans JCM 14343 - Daisuke Inoue; Tsubasa Tsunoda; Norifumi Yamamoto; Michihiko Ike; Kazunari Sei (Biodegradation, 2018)

Oocyte maturation and active motility of spermatozoa are triggered by retinoic acid in pen shell Atrina pectinata - Masahiko Awaji; Toshie Matsumoto; Daisuke Ojima; Shunsuke Inoue; Michio Suzuki; Masaei Kanematsu (Fisheries Science, 2018)

Reinereins A and B, new onocerane triterpenoids from Reinwardtiodendron cinereum - Alfarius Eko Nugroho; Daisuke Inoue; Chin Piow Wong; Yusuke Hirasawa; Toshio Kaneda; Osamu Shirota; A. Hamid A. Hadi; Hiroshi Morita (Journal of Natural Medicines, 2018)

Improved control of black rot of broccoli caused by Xanthomonas campestris pv. campestris using a bacteriophage and a nonpathogenic Xanthomonas sp. strain - Hirofumi Nagai; Noriyuki Miyake; Shinro Kato; Daisuke Maekawa; Yasuhiro Inoue; Yuichi Takikawa (Journal of General Plant Pathology, 2017)

Kinetics of NADP+/NADPH reduction–oxidation catalyzed by the ferredoxin-NAD(P)+ reductase from the green sulfur bacterium Chlorobaculum tepidum - Daisuke Seo; Masaharu Kitashima; Takeshi Sakurai; Kazuhito Inoue (Photosynthesis Research, 2016)

1,4-Dioxane degradation potential of members of the genera Pseudonocardia and Rhodococcus - Daisuke Inoue; Tsubasa Tsunoda; Kazuko Sawada; Norifumi Yamamoto; Yuji Saito; Kazunari Sei; Michihiko Ike (Biodegradation, 2016)

Response of a phytoplankton community to nutrient addition under different CO2 and pH conditions - Takeo Hama; Tomoki Inoue; Risa Suzuki; Hiroto Kashiwazaki; Shigeki Wada; Daisuke Sasano; Naohiro Kosugi; Masao Ishii (Journal of Oceanography, 2016)

Approaches to Quality Risk Management When Using Single-Use Systems in the Manufacture of Biologics - Akiko Ishii-Watabe; Akihiko Hirose; Noriko Katori; Norikata Hashii; Susumu Arai; Hirotoshi Awatsu; Akira Eiza; Yoshiaki Hara; Hideshi Hattori; Tomomi Inoue; Tetsuya Isono; Masahiro Iwakura; et al. (AAPS PharmSciTech, 2015)

Different acute toxicity of fipronil baits on invasive Linepithema humile supercolonies and some non-target ground arthropods - Daisuke Hayasaka; Naoki Kuwayama; Azuma Takeo; Takanobu Ishida; Hiroyuki Mano; Maki N. Inoue; Takashi Nagai; Francisco Sánchez-Bayo; Koichi Goka; Takuo Sawahata (Ecotoxicology, 2015)

Ecological impacts on native ant and ground-dwelling animal communities through Argentine ant (Linepithema humile) (Hymenoptera: Formicidae) management in Japan - Maki N. Inoue; Fuki Saito-Morooka; Kazutaka Suzuki; Takuji Nomura; Daisuke Hayasaka; Toshio Kishimoto; Katsuo Sugimaru; Takashi Sugiyama; Koichi Goka (Applied Entomology and Zoology, 2015)

High-Throughput DNA Microarray Detection of Pathogenic Bacteria in Shallow Well Groundwater in the Kathmandu Valley, Nepal - Daisuke Inoue; Takuji Hinoura; Noriko Suzuki; Junqin Pang; Rabin Malla; Sadhana Shrestha; Saroj Kumar Chapagain; Hiroaki Matsuzawa; Takashi Nakamura; Yasuhiro Tanaka; Michihiko Ike; Kei Nishida; et al. (Current Microbiology, 2015)

Development of a whole community genome amplification-assisted DNA microarray method to detect functional genes involved in the nitrogen cycle - Daisuke Inoue; Junqin Pang; Masami Matsuda; Kazunari Sei; Kei Nishida; Michihiko Ike (World Journal of Microbiology and Biotechnology, 2014)

IRF8 is a transcriptional determinant for microglial motility - Takahiro Masuda; Nao Nishimoto; Daisuke Tomiyama; Tsuyoshi Matsuda; Hidetoshi Tozaki-Saitoh; Tomohiko Tamura; Shinichi Kohsaka; Makoto Tsuda; Kazuhide Inoue (Purinergic Signalling, 2014)

Isolation and characterization of bacterial strains that have high ability to degrade 1,4-dioxane as a sole carbon and energy source - Kazunari Sei; Keiko Miyagaki; Takashi Kakinoki; Kunihiro Fukugasako; Daisuke Inoue; Michihiko Ike (Biodegradation, 2013)

Protein kinase D2 and heat shock protein 90 beta are required for BCL6-associated zinc finger protein mRNA stabilization induced by vascular endothelial growth factor-A - Daisuke Miwa; Tomohisa Sakaue; Hirofumi Inoue; Nobuaki Takemori; Maki Kurokawa; Shinji Fukuda; Kazuya Omi; Katsutoshi Goishi; Shigeki Higashiyama (Angiogenesis, 2013)

Plasmid-mediated bioaugmentation of sequencing batch reactors for enhancement of 2,4-dichlorophenoxyacetic acid removal in wastewater using plasmid pJP4 - Hirofumi Tsutsui; Yasutaka Anami; Masami Matsuda; Kurumi Hashimoto; Daisuke Inoue; Kazunari Sei; Satoshi Soda; Michihiko Ike (Biodegradation, 2013)

Properties of lead deposits in cell walls of radish (Raphanus sativus) roots - Hiroshi Inoue; Daisuke Fukuoka; Yuri Tatai; Hiroyuki Kamachi; Manabu Hayatsu; Manami Ono; Suechika Suzuki (Journal of Plant Research, 2013)

Possible involvement of genotoxic mechanisms in estragole-induced hepatocarcinogenesis in rats - Yuta Suzuki; Takashi Umemura; Daisuke Hibi; Tomoki Inoue; Meilan Jin; Yuji Ishii; Hiroki Sakai; Takehiko Nohmi; Tokuma Yanai; Akiyoshi Nishikawa; Kumiko Ogawa (Archives of Toxicology, 2012)

Impacts of gene bioaugmentation with pJP4-harboring bacteria of 2,4-D-contaminated soil slurry on the indigenous microbial community - Daisuke Inoue; Yuji Yamazaki; Hirofumi Tsutsui; Kazunari Sei; Satoshi Soda; Masanori Fujita; Michihiko Ike (Biodegradation, 2012)

A multiple-isotope (δ37Cl, 14C, 3H) approach to reveal the coastal hydrogeological system and its temporal changes in western Kyushu, Japan - Tomochika Tokunaga; Jun Shimada; Yuki Kimura; Daisuke Inoue; Katsuro Mogi; Kazumi Asai (Hydrogeology Journal, 2011)

Evaluation of the biodegradation potential of 1,4-dioxane in river, soil and activated sludge samples - Kazunari Sei; Takashi Kakinoki; Daisuke Inoue; Satoshi Soda; Masanori Fujita; Michihiko Ike (Biodegradation, 2010)

Detection of Agonistic Activities Against Five Human Nuclear Receptors in River Environments of Japan Using a Yeast Two-Hybrid Assay - Daisuke Inoue; Koki Nakama; Hisae Matsui; Kazunari Sei; Michihiko Ike (Bulletin of Environmental Contamination and Toxicology, 2009)

Sugar receptor response of the food-canal taste sensilla in a nectar-feeding swallowtail butterfly, Papilio xuthus - Takashi A. Inoue; Kiyoshi Asaoka; Kazuaki Seta; Daisuke Imaeda; Mamiko Ozaki (The Science of Nature, 2009)

Adenosine modulates excitatory synaptic transmission and suppresses neuronal death induced by ischaemia in rat spinal motoneurones - Nobuyuki Miyazaki; Terumasa Nakatsuka; Daisuke Takeda; Kazuhiro Nohda; Kazuhide Inoue; Munehito Yoshida (Pflügers Archiv - European Journal of Physiology, 2008)

In situ strength measurements on natural upper-mantle minerals - Junji Yamamoto; Jun-ichi Ando; Hiroyuki Kagi; Toru Inoue; Akihiro Yamada; Daisuke Yamazaki; Tetsuo Irifune (Physics and Chemistry of Minerals, 2008)

Anaerobic biodegradation of polychlorinated biphenyls by a microbial consortium originated from uncontaminated paddy soil - Daisuke Baba; Tsuyoshi Yasuta; Naoko Yoshida; Yuko Kimura; Katsuhide Miyake; Yasushi Inoue; Koki Toyota; Arata Katayama (World Journal of Microbiology and Biotechnology, 2007)

Comparative Evaluation of Quantitative Polymerase Chain Reaction Methods for Routine Enumeration of Specific Bacterial DNA in Aquatic Samples - Daisuke Inoue; Katsushi Wada; Kazunari Sei; Michihiko Ike; Masanori Fujita (World Journal of Microbiology and Biotechnology, 2005)

Abstract of Poster Presentation - Hiroshi Uchida; Tetsuo Maruyama; Jkuko Sugiura; Takashi Kajitani; Touru Arase; Masanori Ono; Takashi Nagashima; Hirotaka Masuda; Hironori Asada; Yasunori Yoshimura; Soichiro Saito; Mila Ghosh; et al. (Human Cell, 2005)

Purification and characterization of ferredoxin-NADP+ reductase encoded by Bacillus subtilis yumC - Daisuke Seo; Kei Kamino; Kazuhito Inoue; Hidehiro Sakurai (Archives of Microbiology, 2004)